2022
DOI: 10.1002/bse.3306
|View full text |Cite
|
Sign up to set email alerts
|

Organic food consumption and contextual factors: An attitude–behavior–context perspective

Abstract: This study is grounded within the theoretical framework of attitude–behavior–context. The study examines how perceived health risk shapes both health and environmental attitudes, leading to organic food consumption. Further, we also assess the role of perceived effectiveness and green trust in moderating the proposed relationships. The data were collected from 461 consumers through Amazon Mechanical Turk platform. Our findings indicate that consumers' perception of health risk plays a significant role in devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 94 publications
(183 reference statements)
0
8
0
Order By: Relevance
“…To increase the accuracy of the e-survey and its results, strict inclusion criteria are recommended (Sadiq et al. , 2021, 2023). In this study, respondents were only eligible if they had used e-commerce platforms in the past three months (Dogra et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the accuracy of the e-survey and its results, strict inclusion criteria are recommended (Sadiq et al. , 2021, 2023). In this study, respondents were only eligible if they had used e-commerce platforms in the past three months (Dogra et al.…”
Section: Methodsmentioning
confidence: 99%
“…Following the suggestions of Rafiq et al (2022a, b), we approached respondents for data collection using an e-survey. To increase the accuracy of the e-survey and its results, strict inclusion criteria are recommended (Sadiq et al, 2021(Sadiq et al, , 2023. In this study, respondents were only eligible if they had used e-commerce platforms in the past three months .…”
Section: Ijrdm 5112mentioning
confidence: 99%
“…In addition, the model gauges the role of uncertainty avoidance (UA) as a moderator between ATT, SN, PBC and intention (IN) [24,25]. This conceptual model offers a focused outlook on sustainable consumption, and takes a more conscientious approach to nature management, which will benefit present and future generations [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, some scholars have claimed that there exists an intention–behavior gap in organic consumption (Bosquez and Arias-Bolzmann, 2022; Cheah and Aigbogun, 2022; Juhl et al ., 2017; Shamsi et al ., 2020). It is reported that even though the consumers express strong intentions to consume organic food, these intentions do not convert into actual purchasing behavior (Cheah and Aigbogun, 2022; Sadiq et al ., 2022). Therefore, to improve this intention–behavior gap and better predict the organic purchase behavior, some scholars have supplemented some constructs to the TPB.…”
Section: Introductionmentioning
confidence: 99%